Oral extranodal non hodgkin's lymphoma: Series of forty two cases in Malaysia - Ramanathan, A.; Mahmoud, H.A.; Hui, L.P.; Mei, N.Y.; Valliappan, V.; Zain, R.B. (2014)
Background: Lymphoma is a malignant neoplasm of lymphoid tissue classified into Hodgkin's and non-Hodgkin's types. It mostly affects lymph nodes although a considerable proportion of Non-Hodgkin's cases occur in extranodal sites. Materials and Methods: Selected cases diagnosed as non-Hodgkin's lymphoma (NHL) during the period of 1980 to 2012 were retrieved from the archives of the Oral Pathology Diagnostic Laboratory, Faculty of Dentistry, University of Malaya. The sections from the formalin-fixed paraffin embedded tissue blocks were stained with H&E as well as with LCA, CD20, and CD3. Results: The mean age was 41.6 years with a male: female ratio of 1.3:1. Out of the forty two cases, nineteen were Malays, eighteen were Chinese, followed by Indians (3) and Indonesians (2). The most common site of involvement was the mandible (22.2%), followed by the maxilla and palate (19.4% each). Most of the lesions presented as a painless progressive swelling. Only thirty six cases were further subdivided into B or T cell types. The majority were B-cell type (26 cases), of these 6 cases were Burkitt's lymphomas. Only ten cases were T-cell lymphoma, with three cases of NK/T-cell lymphoma. Conclusions: In this series of 42 patients diagnosed as extranodal non-Hodgkin's lymphoma, the lesions appeared as painless swellings, mostly in men with the mandible as the most frequent site of involvement. Majority were B-cell lymphomas with Malays and Chinese being equally affected whereas lymphomas were rare in the Indian ethnicity. T-cell lymphomas were found to be common in the Chinese ethnic group.